Functional and esthetic rehabilitation during deciduous dentition stage: A case report - Sheeba Saini; Deepak Sharma (Wolters Kluwer Medknow Publications, 2011)
A virtual absence of palliative, preventive and restorative care characterizes juvenile oral health care in most of the developing and underdeveloped countries. Consequently, carious cavities remain untreated, which leads to pain, discomfort and functional limitation. It further, impacts negatively upon general health and cognitive development apart from causing decreased masticatory efficiency, difficulty in speech, compromised esthetics, development of abnormal tongue habits and subsequent malocclusion and psychological problems. The restoration of severely decayed deciduous teeth especially anterior ones presents a major challenge to dentists, particularly in uncooperative children. The following case report documents the restoration of severely mutilated deciduous teeth in an emotionally immature patient resulting in an improvement in not only his oral and general health also in helping him gain more self-confidence.